Improvement of Sheep Reproductive Performance in Livestock Groups Through Flushing Applications Locally Sourced in Banyusidi Village - Utomo, Setyo; Sudrajat, Ajat; Rasminati, Nur; Nugroh0, Bambang (Farmers : Journal of Community Services, 2026)
Community Partnership Service activities have been carried out in the Abita Farm sheep business group and the Berkah Makmur livestock group, Banyusidi village, district, Magelang from May to November 2025. The problem in these two groups is the low reproductive efficiency, namely giving birth 2 times in 2 years, which should be 3 times in 2 years for sheep.  The solution to this problem is the use of egg yolks mixed with MOL (Local Micro Organisms) rice as feed flushing, rice MOL making, making a reproductive calendar and flushing techniques. The methods applied are awareness, training, flushing application, evaluation of flushing results and making MOL and mentoring. Flushing technology is applied using egg yolks mixed with MOL given as additional feed to prospective and non-pregnant sheep for 10 days with a dose of 7ml of egg yolk mixed with 5 ml of MOL/head/day, then observation of growth and the onset of bile.  Livestock that are greedy are mated by nature.  The results achieved in the Abita Farm group after 10 days of flushing sheep with an average age of 2.2 years showed that 50% were fertile and immediately mated naturally, while the body weight gain was relatively fixed.  In the Berkah Makmur group with an average age of 2.15 years, 55% experienced lustfulness and an increase in body weight of 189.25 g/day.  The average level of satisfaction of participants showed 22% satisfied and 78% very satisfied with the results of flushing and the ability to apply in sheep farming. To ensure the sustainability of this activity, it is coordinated with the Magelang Regency Livestock and Fisheries Office. It was concluded that the provision of flushing of mixed egg yolk-MOL feed precisely ensures good growth and growth, especially in sheep that are only given forage.